Diary Writing as a Queer Technology of the Self: David Vilaseca’s Els homes i els dies - Álvaro González Montero (InterAlia)
This paper examines David Vilaseca’s Els homes i els dies from a Foucauldian perspective, applying Foucault’s concept of “technologies of the self” to queer diary writing and establishing a dialogue with Vilaseca’s own theoretical oeuvre. Firstly, the notion of universality of the queer experience that Vilaseca endeavoured to explore in his academic work is complicated by looking at the author’s diary writing in combination with theoretical approaches from authors such as Edelman, Laclau and Muñoz, as well as Vilaseca’s theory itself, amongst others. Secondly, the practice of writing one’s own life, including the reasons behind it and its purposes, is examined. This paper demonstrates the queer sensibility behind Vilaseca’s diary writing practice. It also complicates said queerness by showing the ethical, affective, and spatial implications of diary writing. Thus, a complex landscape of autobiographical self-reflection is laid out, where there is more than just resistance or subversion in Vilaseca’s Els homes i els dies. By closely analysing the tensions and connections between the notions of universality and particularity, resistance and integration, kinship and individualism, under the light of a range of theoretical approaches, such as psychoanalysis and queer narrative theory, this article provides a comprehensive picture of this example of queer, Catalan life-writing in the last decade of the twentieth century.